Theoretical Views on the Category of Place/Space: Analysis and Relationship (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the linguistic category of space by analyzing theoretical approaches from classical and contemporary linguistics. It examines the semantic, pragmatic, cognitive, and linguocultural dimensions of space as reflected in language. The study highlights the role of locative expressions, and culturally specific perceptions of space across languages. The relevance of spatial categorization in shaping linguistic worldview and cultural identity is emphasized. The article also underlines the importance of studying space from a cross-linguistic and interdisciplinary perspective to better understand its conceptual and communicative functions.